Baseline Characteristics And Outcome Of Covid-19 Patients In Bangladesh (Journal of Preventive and Social Medicine, 2024)
Background: Coronavirus disease-2019 (COVID-19) is the disease caused by Severe Acute Respiratory Syndrome Corona virus 2 (SARS-CoV-2). The disease was declared as a pandemic by WHO in a press release on 11 February 2020. The virus was confirmed to have spread to Bangladesh in March 2020. To combat this pandemic disease, baseline characteristics of the COVID-19 patients are essential to be identified in the context of Bangladesh.Methods: The cross-sectional study was conducted among 1016 COVID-19 patients diagnosed by Reversed Transcriptase-Polymerase Chain Reaction (RT-PCR) assay at the National Institute of Preventive and Social Medicine (NIPSOM) laboratory. The study was conducted during the period from March to June 2020, Data were collected form the participants, who were selected conveniently and were interviewed by using a pre-tested semi-structured questionnaire over telephone.Results: The study revealed that among 1016 respondents, 64.1% were male and the rest 35.9% were female. Almost half of the respondents (46.5%) were aged 19-39 years. Among the respondents, 72.6% were married and 39.6% were graduated and above. More than two-thirds (69.3%) of the respondents lived in urban area and 72.7% were from nuclear family. On the fourteenth (14th) day or onwards of being positive, RT–PCR Test-1 found 12.5% positive and on twenty-eighth (28th) day or onwards RT–PCR Test-2 found positive only 3.3%. On the other hand, RT–PCR Test-1 was not done by 11.6% and RT–PCR Test-2 by 41.8%. While on the fourteenth (14th) day or onwards of being positive, 62.1% patients were continuing treatment and on the twenty-eighth (28th) day or onwards only 3.5% patients were continuing treatment due to covid related complications.Conclusion: Baseline characteristics, severity and outcomes of sequentially tested patients with confirmed COVID-19 positive cases in Bangladesh. Such information should be disseminated across the country to raise awareness and initiate necessary measures by the policy makers to prevent spread of corona virus in Bangladesh.JOPSOM 2021; 41(2):36-42